Quantum chemical investigation of spectroscopic, electronic and NLO properties of (1E, 4E)-1-(3-nitrophenyl)-5-phenylpenta-1,4-dien-3-one - Benhalima, N; Yahiaoui, S; Boubegra, N; Boulakoud, M; Megrouss, Y; Chouaih, A; Hamzaoui, F (International Journal of Advanced Chemistry, 2018)
In the present work the optimized molecular geometry and harmonic vibrational frequencies of chalcone derivative were calculated by DFT/B3LYP method with 6–31G (d,p) basis set. The vibrational assignments were performed on the basis of the potential energy dis-tribution (PED) of the vibrational modes. Natural bond orbital (NBO) analysis has been performed on title compound using B3LYP/6–31G (d,p) and HSEh1PBE /6–31G (d,p) levels in order to elucidate intermolecular hydrogen bonding, intermolecular charge transfer (ICT) and delocalization of electron density. Mulliken atomic charges, natural population analysis (NPA) and atomic polar tensors (APT) were performed. The nonlinear optical properties of the title compound are also calculated and discussed. Molecular electrostatic poten-tial and HOMO-LUMO energy levels are also computed. Ultraviolet–visible spectrum of the title compound has been calculated using TD–DFT method. The molecular orbital contributions were studied by density of states (DOSs). Global reactivity descriptors have been calculated using the HOMO and LUMO to predict compound reactivity.